A glass ceiling on poverty reduction? An empirical investigation into the structural constraints on minimum income protections. (May 2020) - Cantillon, Bea; Parolin, Zachary; Collado, Diego
This article investigates whether declining or sluggish growth in earnings for low-wage workers contributes to declining levels of minimum income protections. Starting from the observation of lacklustre growth in minimum income protections, this article introduces a framework to conceptualize the tensions facing modern welfare states in their attempt to (1) provide poverty-alleviating minimum incomes, (2) achieve employment growth and (3) keep spending levels in check. We argue that, due to downward pressure on low gross wages compared to median household incomes, it has become more difficult to balance each of those three objectives. Estimation results from country-year panel data suggest that declines in minimum wages (or low gross wages) are associated with declines in minimum income protections for the jobless. When growth in minimum income protections does exceed growth in low gross wages, we find that welfare states also increase gross-to-net effort to subsidize the net income of low-wage earners. We argue that these findings point towards a 'structural inadequacy' around minimum income protections for the jobless.